Volume One 2012-13 - GREY NOISE (Dubai; Grey Noise Art Gallery, 2013)
Exhibition catalog. This is the first volume documenting the programme at the new Grey Noise space. Grey Noise is a contemporary art gallery representing a selection of artists, with a focus on work from South Asia and Europe. Texts: Ehsan ul Haq, Iqra Tanveer, Mehreen Murtaza, Fahd Burki, Michael John Whelan, Ayesha Jatoi, Fahd Burki
English
Keywords: N4390-5098 Visual Arts. Exhibitions; UAE